A new species of freshwater amphipod (Crustacea, Peracarida, Hyalellidae) from Southern Brazil - Limberger, Marcio; Da Silva Castiglioni, Daniela; Graichen, Daniel Ângelo Sganzerla (Zootaxa, 2021)
The freshwater amphipod of the genus Hyalella is typical from continental American waters and shows high levels of endemicity and Brazil has the second largest diversity. A new species is described here, Hyalella longipropodus n. sp. that occurs in a spring of southern Brazil in the municipality of Palmeira das Missões, in the northwestern region of state of Rio Grande do Sul, southern Brasil. Hyalella longipropodus n. sp. shows the following character states: antenna 2 more than half body length, gnathopod 2 propodus elongated, uropod 1 inner ramus of male without apical curved setae, uropod 3 peduncle with seven strong distal setae with accessory setae, ramus of uropod 3 with ten cuspidate setae with accessory setae. Hyalella longipropodus n. sp. occurs in sympatry with H. gauchensis, but these differ especially in the size and shape of gnathopod 2, the presence of curved setae on uropod 1 in H. gauchensis and the absence in H. longipropodus n. sp., antenna length (longer in H. longipropodus n. sp.) and number of cuspidate setae on uropods 1, 2, and 3. Besides the morphological differences, H. longipropodus n. sp. presented genetic differences always above 19% for the COI gene and 29 % for the 16S rRNA gene, when compared with other species found in the northwestern region of the state of Rio Grande do Sul, showing that it is really a species not yet described by science.